2022
DOI: 10.1021/acsaem.2c03525
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Energy Storage Performances in PMMA/PVDF Nanocomposites with Low Dielectric Bismuth Carbonate Nanosheets

Abstract: Both high discharge energy density (U d ) and charge−discharge efficiency (η) for nanocomposites are crucial to the development and application of modern electronic devices. However, the large dielectric contrast and ferroelectric phase greatly limit the improvement of U d and η of poly(vinylidene fluoride) (PVDF)-based nanocomposites. Herein, Bi 2 O 2 CO 3 (simplified as BOC) nanosheets with low dielectric constant and wide bandgaps and linear poly(methyl methacrylate) (PMMA) were filled into PVDF by solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…This demonstrates that PVDF and PMMA have high miscibility and compatibility. Previous research [31][32][33] found that the two polymers, PVDF and PMMA, have very similar solubility parameters of 22.7 and 23.2 [34], respectively. Moreover, their compatibility with each other is excellent.…”
Section: Resultsmentioning
confidence: 95%
“…This demonstrates that PVDF and PMMA have high miscibility and compatibility. Previous research [31][32][33] found that the two polymers, PVDF and PMMA, have very similar solubility parameters of 22.7 and 23.2 [34], respectively. Moreover, their compatibility with each other is excellent.…”
Section: Resultsmentioning
confidence: 95%
“…From the cross-sectional image (figure 2(d)), no obvious holes or defects could be observed in the 0 wt.% Ni(OH) 2 BPB nanocomposite, and Ni(OH) 2 absence in middle layer indicates successfully preparing the sandwich-structured nanocomposite. Meanwhile, the dense structure of x wt.% Ni(OH) 2 BPB nanocomposites (figure S3) might help to prevent premature localized breakdown at the gaps [4]. Therefore, the prepared nanocomposites have a high quality, indicating their potential for high energy storage performances.…”
Section: Resultsmentioning
confidence: 99%
“…With modern electronic technology advancement, the demand for dielectric capacitors possessing high discharge energy density (U d ) and charge-discharge efficiency (η) has rapidly increased [1][2][3][4][5][6]. However, compared with other energy storage devices [7,8], the current polymer dielectric materials * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Study of complex dielectric permittivity ε * = εʹ−jε″ over the broadband frequency range of the PNC materials is highly meaningful to understand the various polarization and dynamical processes in the complex system, and also to explore their uses as innovative nanodielectrics in the design and development of flexible type microelectronic devices [1, 3−6, 15, 24, 41, 53, 57-60]. In addition to this, with the help of laboratory measured experimental values of the dielectric parameters at different frequencies, the applications of such nanodielectric materials can be fixed as prominent energy storage and insulator materials in the harmonic electric field operative electronic devices [3,12,57,58,60,61]. The measured dielectric permittivity (i.e.…”
Section: Dielectric Dispersion and Relaxation Behaviourmentioning
confidence: 99%